Bullous pemphigoid and neurological disease: statistics from a dermatology service - Monica Jidid Mateus Tarazona; Amanda Nascimento Cavalleiro de Macedo Mota; Alexandre Carlos Gripp; Natasha Unterstell; Aline Lopes Bressan (Anais Brasileiros de Dermatologia, 2015)
Bullous pemphigoid (BP) is an autoimmune, acquired, cutaneous disease caused by the production of autoantibodies against hemidesmosomes' components in the basement membrane. The estimated incidence in Europe ranges from 7 to 43 cases per million inhabitants per year. Several studies have reported an association between BP and neurological disorders (ND). Our cohort of Bullous pemphigoid and ND is the first in Brazil and showed a significantly high prevalence of neurological and/or psychiatric diseases, especially cerebrovascular accident (CVA) and dementia, in agreement with the prevalence reported in several studies published in the medical literature in recent years.